Hubungan Kepatuhan Perawat dalam Melakukan Monitoring Formulir Early Warning Scoring System (EWSS) dengan Kejadian Code Blue di Ruangan Perawatan Umum - Dhestri Setia Sari; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (PPNI UNIMMAN, 2026)
Early Warning Score (EWS) is early detection instrument for predicting severity or worsening of a patient's condition. Therefore, nurses' compliance with the assessment is crucial. The goal is to reduce the incidence of code blues in general care units. Code blue is a procedure code used for conditions where a victim is found to be at risk of cardiac arrest or respiratory arrest. Methods: This study is a quantitative analytical survey, a form of research that examines the effects and risk factors. The study design was cross-sectional, examining the dynamics of correlation between dependent and independent variables. The number of respondents in this study was 150, drawn from a total sampling of the nurse population in general care units. The data obtained were subjected to statistical analysis using a non-parametric Chi-Square test. Results: Respondents, based on their level of compliance with the EWSS monitoring form, were mostly in the compliant category (94%), and most had an impact on the absence of code blues (94%) in the emergency risk group. Conclusion: There is a significant relationship between nurses' compliance in monitoring the completion of the EWSS and the occurrence of code blue in inpatient rooms (P-Value <0.05).